2018
DOI: 10.36232/jurnalpendidikanbahasa.v5i2.182
|View full text |Cite
|
Sign up to set email alerts
|

THE EFFECTIVENESS OF STORYTELLING STRATEGY TO IMPROVE STUDENTS’ READING COMPREHENSION AT SECOND GRADES OF MTs AL-MA’ARIF 1 KABUPATEN SORONG

Abstract: This research aimed to know the effectiveness of storytelling strategy to improve the students’ reading comprehension at second grades of MTs Al-Marif 1 KabupatenSorong. Storytelling was one of the good strategy in teaching learning process especially in teaching reading, because it can make the student was easier to understand about the text/story. In this research, the researcher used Quasi-experimental design. The subject of this research was VIIIC as experiment class that consist of 30 students: 16 males a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…Most of them felt helpful by the application of High Five strategies to help them read. Its also has same definition to what Hatam, Sudibyo, & Wibowo (2018) said that the teacher are going to make the student enjoy in teaching learning process.…”
Section: Findings and Discussionmentioning
confidence: 94%
“…Most of them felt helpful by the application of High Five strategies to help them read. Its also has same definition to what Hatam, Sudibyo, & Wibowo (2018) said that the teacher are going to make the student enjoy in teaching learning process.…”
Section: Findings and Discussionmentioning
confidence: 94%
“…It starts from the moving of words on the page to meaning in the mind, the recognizing of individuals words by using memory and knowledge of letter and sounds patterns, matching the resulting pronunciations to meaning, and finally connect these words into idea units. Sudibyo, Wibowo, Hatam (2018) comment that reading comprehension is useful to help the students for gaining the information about the text that they read. It can be concluded that that reading comprehension is a process of students in understanding a text.…”
Section: Reading Comprehensionmentioning
confidence: 99%